Civic Defense as A Method to Prevent The Threat of Radicalism in Indonesia - Indrawan, Raden Mas Jerry; Efriza, Efriza (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2017)
Terrorism, rooted in radical movement post 9/11 event in the United States, began to grow rapidly also in Indonesia. Radical movements, especially those based on religion, evolved into terrorist movements that threaten state security and defense. Civic education is part of the implementation ofÂ  state defense and security system. Radicalism, both as a movement and an ideology or a growing notion among Indonesians, is a threat to the state, that has a non-conventional nature. Therefore, civic education can be a program that can change peopleâ€™s culture to put the love of the nation and the country as the main thing, thereby preventing the development of radical movements and ideology in Indonesia. The elements of religiosity (religion) can also play an important role in counteracting the threat of radicalism if it is integrated into the civic education curriculum. This paper will look at how civic education program can be used as a means of preventing the threat of radicalism in Indonesia.